Konflik Politik Negatif dalam Novel Pulang Karya Leila S. Chudori - Melati Sukma Dewi; Nazla Maharani Umaya; Setia Naka Andrian (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to describe the negative political conflict in the novel Pulang by Leila S. Chudori using Ramlan Surbakti's conflict theory. The focus of this study is on the forms of negative political conflict. This novel represents Indonesian political history, especially the events of 1965 and the 1998 reformation. The method used is qualitative with a mimetic approach. In this study, reading and listening techniques are used to collect research data in the form of quotations in the novel related to negative political conflict. This research is presented using qualitative descriptive techniques. The results of this study show the forms of negative political conflict in the form of conflicts in the struggle for power and conflicts in maintaining power. Negative political conflict involves parties including conflicts between political parties and state apparatus, conflicts between state apparatus and state leaders, conflicts between civil society and the government, and conflicts between academics and state leaders.